The Role of Health Information in Managing Health Services Efficiently and Effectively (Health Information - Managing Health Services) - Alshalwi, Awwadh Ghazi; Almazni, Mazen Abdullah; Alzahrani, Asrar Ahmed Bkheit; Alwadai, Amnah Ali A; Almowalid, Myaid Ali F (Journal of Posthumanism, 2025)
The systematic management of health information has evolved from an ancillary support function into a core strategic driver of efficiency and effectiveness in modern healthcare. This paper examines the multifaceted role of health information in enabling superior management of health services. It begins by defining the foundational concepts of health information, health informatics, and Health Information Systems (HIS), detailing the transition from paper-based records to integrated digital ecosystems. The analysis demonstrates how accurate, timely, and accessible information underpins data-driven decision-making, strategic planning, and performance evaluation. The paper explores the application of data analytics, business intelligence, and key performance indicators in translating raw data into actionable intelligence for optimizing resource allocation and improving clinical workflows. Furthermore, it investigates strategies for enhancing system performance through technological innovation—such as artificial intelligence and big data—and through critical organizational factors, including leadership commitment, change management, and workforce capacity building. The central conclusion is that continuous, strategic investment in robust and interoperable HIS is not merely a technological imperative but a fundamental prerequisite for achieving sustainable improvements in patient care, operational performance, and population health outcomes.